First report of linear megaplasmids in the genus Micrococcus. Plasmid (2009), - Dib, Julian Rafael (2010)
High-altitude wetlands (above 4200 m) in the northwest of Argentina are considered pristine and extreme environments. Micrococcus sp. A1, H5, and V7, isolated from such environments, were shown to contain linear megaplasmids, designated pLMA1, pLMH5, and pLMV7, respectively. As known from linear plasmids of other actinomycetes, all three plasmids were resistant to k exonuclease treatment, which is consistent with having terminal proteins covalently attached to their 50 DNA ends. Electrophoretic mobility, Southern analysis, and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. proteins covalently attached to their 50 DNA ends. Electrophoretic mobility, Southern analysis, and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. and restriction endonuclease patterns revealed pLMA1 and pLMH5 being indistinguishable plasmids, even though they were found in different strains isolated from two distant wetlands – Laguna Azul and Laguna Huaca Huasi. Analysis of 16S rDNA sequences of Micrococcus sp. A1, H5, and V7 suggested a close relationship to Micrococcus luteus. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed using fingerprint patterns generated by BOX-PCR. Plasmid- deficient strains, generated from Micrococcus sp. A1, showed a significantly decreased resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. resistance level for erythromycin. Typing of isolates was performed